Modeling of hot air drying of coconut residue - Pattawee Wutthigarn; Jeerayut Hongwiangjan; Jiraporn Sripinyowanich Jongyingcharoen (My University, 2018)
In this study, the effect of drying temperature (50-110°C) on hot air drying characteristics of coconut residue was investigated. The drying time and drying rate (DR) were in the ranges of 540-100 min and 0.0048-0.0182 g water/g dry matter·min at the drying temperature of 50-110°C, respectively. Six drying models (Lewis, Page, Henderson and Pabis, Logarithmic, Midilli et al, and linear-plus-exponential model) were used to determine the change in moisture ratio (MR) with drying time. The linear-plus-exponential model provided best fitting of the predicted MR to the experimental MR with the highest average R 2 of 0.9985 and the lowest RMSE of 0.01463. The variation of drying temperature with the constants and coefficient of the model was polynomial type. The generalized linear-plus-exponential model as a function of drying temperature gave best result of prediction of MR with the R 2 of 0.9709.
Keywords: Residue (chemistry); Food Drying and Modeling